Predicting the present and future of aquaponics with google trends - Dos Santos, Maria José Palma Lampreia (2017)
Aquaponics is an innovative scientific and professional area in Europe and across the world with increasing importance. However, despite the importance of aquaponics in Europe and in the world to promote safely and fresh foods, there is a gap because stakeholders, researchers and other professionals don’t really know the actual development and http://repositorio.ipl.pt/increasing of importance this activity in Europe despite the enormous contribution of the Aquaponics Hub from COST FA 1305. To overcome this problem and to know about the status, trends and importance of aquaponics searching in Europe we conduct this work. The main goal is to analyses the aquaponics and aquaponics related terms search through Google trends tool across the European countries where the Aquaponics Hub from COST FA 1305 where present from 2014 to the present, in order to analyses the path of aquaponics and the contribute done by the Action COST FA 1305 and related research. The methodology includes univariate and econometric models based on google trends from 2014 to the present. The results high line confirms the increasing trends of aquaponics and aquaponics related terms across the Europe and European countries belongs to COST FA 1305, but there are significant differences among countries. In general, the results per country show a real increasing after the countries becoming member of the present action of the COST action or an increasing during the Action, but there are differences among countries country. As well the increasing of scientific papers indexed in SCOPUS or Web of Science was increasing.